2019
DOI: 10.26434/chemrxiv.9333212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reproducible Molecular Networking Of Untargeted Mass Spectrometry Data Using GNPS.

Abstract: Herein, we present a protocol for the use of Global Natural Products Social (GNPS) Molecular Networking, an interactive online chemistry-focused mass spectrometry data curation and analysis infrastructure. The goal of GNPS is to provide as much chemical insight for an untargeted tandem mass spectrometry data set as possible and to connect this chemical insight to the underlying biological questions a user wishers to address. This can be performed within one experiment or at the repository scale. GNPS not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 0 publications
0
88
0
12
Order By: Relevance
“…Out of 89 metabolites, only 22 were identified based on the molecular networking database. Eight metabolites were found to be reliable and are considered, as shown in Table 1 [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 89 metabolites, only 22 were identified based on the molecular networking database. Eight metabolites were found to be reliable and are considered, as shown in Table 1 [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings were in line with those of Debashis et al (2016) [ 21 ], who reported that A. pinnata reduces serum activities of ALT and AST. The ameliorative effects of A. pinnata against lead acetate-induced hepatotoxicity may be attributed to the antioxidant and anti-inflammatory activities of its constituents as 10 metabolites were found to be reliable ( Figure 3 and Figure 4 , Table 1 ) [ 44 ]. A. pinnata ethanolic extract was found to be rich in flavonoids, which are well-known for their antioxidant and anti-inflammatory activities [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…These examples highlight how molecular networking can be used to propagate potential metabolism. How potential metabolism can be inferred with molecular networking is explained in (Quinn et al, 2017) and (Aron et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Several computational tools increase our ability to identify unknown compounds through searches and in silico calculations (CSI:FingerID, Dührkop et al, 2019;ClassyFire, Feunang et al, 2016;MetFrag, Ruttkies et al, 2019). The structural similarities in MS 2 spectra have proven especially useful in identifying compounds (MolNetEnhancer, Ernst et al, 2019;MetDNA, Shen et al, 2019;MS2LDA, van der Hooft et al, 2020), which is evident in the expanded list of tools now available at Global Natural Products Social Networking (Wang et al, 2016;Aron et al, 2020). For example, users can search mass spectrometry data using MASST (Wang et al, 2020) and reuse publicly available data via ReDU (Jarmusch et al, 2019).…”
Section: Analysis Of Polar Biologically Labile Organic Moleculesmentioning
confidence: 99%